2016
DOI: 10.1111/cbdd.12714
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Pharmacological Evaluation of Novel Piperlongumine derivatives as Potential Antiplatelet Aggregation Candidate

Abstract: A series of novel piperlongumine derivatives (4a-i, 6a-i) were designed and synthesized. The inhibitory activities of platelet aggregation induced by ADP and AA in vitro have been evaluated by bron turbidimetry and liver microsomal incubated assay. The assay results show that compounds 4e and 6e exhibited remarkable potency to that of the positive control piplartine and aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Piplartine ( 1 ) is an alkamide commonly found in long pepper ( Piper longum L.). Previous reports indicated piplartine exhibited a wide range of pharmacological activities, including anti-diabetic, anti-ulcer, anti-platelet aggregation, anti-atherosclerotic, anti-depressant, anti-bacterial and anti-fungal properties [ 11 , 12 , 13 , 14 ]. Moreover, this compound possesses a highly selective and effective antitumor property, which protects against various types of tumors [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Piplartine ( 1 ) is an alkamide commonly found in long pepper ( Piper longum L.). Previous reports indicated piplartine exhibited a wide range of pharmacological activities, including anti-diabetic, anti-ulcer, anti-platelet aggregation, anti-atherosclerotic, anti-depressant, anti-bacterial and anti-fungal properties [ 11 , 12 , 13 , 14 ]. Moreover, this compound possesses a highly selective and effective antitumor property, which protects against various types of tumors [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Piperlongumine (PL) was originally isolated from fruits of black pepper (Piper nigrum Linn) and long pepper ( Piper longum L.) ( Zhu et al, 2021 ). Cumulative evidence has suggested that PL and its derivatives elicit a broad spectrum of pharmacological activities, including anti-inflammatory ( Sant'Ana et al, 2020 ), neuroprotective ( Bezerra et al, 2013 ; Jung et al, 2013 ; Carreiro et al, 2014 ; Wiemann et al, 2017 ), antioxidant ( Li et al, 2019 ), anti-cancer ( Piska et al, 2018 ; Tripathi and Biswal, 2020 ; Sun et al, 2021 ), antiplatelet aggregation ( Wang et al, 2016 ), anti-diabetes ( Rao et al, 2012 ) and other biological activities. In 2018, Go et al reported PL treatment has been shown to regulate age-related cognitive decline in age correlates and hippocampal dysfunction in elderly mice ( Go et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Piperlongumine ( 1 , Figure ) is an alkaloid isolated from the root of Piper longum L, of which trans -piperlongumine is the main natural stereoisomer . Piperlongumine displays various pharmacological activities, such as anticancer, antiplatelet aggregation, anti-inflammatory, antifungal, and antidepression. Piperlongumine inhibits the proliferation and metastasis of cancer cells in various ways. It induces the production of high levels of ROS, with little influence of ROS in normal cells. ,, Additionally, it is also able to induce cancer cell cycle arrest. Mechanistic studies showed that piperlongumine binds to glutathione (GSH) in cancer cells, leading to an increase in the level of ROS in cancer cells, and that ROS could form more active N-oxide (RNOS) with NO to inhibit cancer.…”
mentioning
confidence: 99%